EKSISTENSI PENGAWAS SEKOLAH DALAM PEMBANGUNAN MUTU SEKOLAH - I Wayan Arka (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
Academic supervision is a form of assistance from supervisors to improve the quality ofschool management and develop the competence of teachers to become professional educators.Efforts to create a good and conducive teaching and learning situation are not denied by variousnegative factors that arise by inhibiting the process to achieve the goals that have been set. Inthe end all organizational activities must be monitored with good, effective, efficient and systematicsupervision. The form of school supervisor services is directed towards improving and improvingthe competence of teachers to be professional educators. For this reason, the presence of schoolsupervisors as supervisors in the education unit is very important to conduct periodic monitoring,in order to build an integrated, patterned and integrated education system so that the goals ofteaching can be achieved. The supervision action is as guidance, not as examiner, so that theform of the problems faced can be solved easily, quickly and unsustainably. As an effort tounderstand deeper and broader, strengthen competence and increase the professionalism ofschool supervisors in the development of school quality and education in general.Keywords: School Supervisor, School Quality